Is soft drink consumption associated with gestational hypertension? Results from the BRISA cohort - Barbosa,J.M.A. (2021)
It is still unknown whether excessive consumption of sugar-sweetened beverages may be linked to gestational hypertensive disorders, other than preeclampsia. This study investigated the association between soft drink consumption and hypertension during pregnancy, analyzing the relationship from the perspective of counterfactual causal theory. Data from pregnant women of the BRISA cohort were analyzed (1,380 in São Luis and 1,370 in Ribeirão Preto, Brazil). The explanatory variable was the frequency of soft drink consumption during pregnancy obtained in a prenatal interview. The outcome was gestational hypertension based on medical diagnosis, at the time of delivery. A theoretical model of the association between soft drink consumption and gestational hypertension was constructed using a directed acyclic graph. Marginal structural models (MSM) weighted by the inverse of the probability of soft drink consumption were also employed. Using Poisson regression analysis, high soft drink consumption (≥7 times/week) was associated with gestational hypertension in São Luís (RR=1.48; 95%CI: 1.03-2.10), in Ribeirão Preto (RR=1.51; 95%CI: 1.13-2.01), and in the two cohorts combined (RR=1.45; 95%CI: 1.16-1.82) compared to lower exposure (<7 times/week). In the MSM, the association between high soft drink consumption and gestational hypertension was observed in Ribeirão Preto (RR=1.63; 95%CI: 1.21-2.19) and in the two cohorts combined (RR=1.51; 95%CI: 1.15-1.97), but not in São Luís (RR=1.26; 95%CI: 0.79-2.00). High soft drink consumption seems to be a risk factor for gestational hypertension, suggesting that it should be discouraged during pregnancy.